2015
DOI: 10.3390/polym7020298
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardance and Physical Properties of Novel Cured Blends of Unsaturated Polyester and Furan Resins

Abstract: Novel blends of two furan resins with an unsaturated polyester have been prepared and cured by parallel free radical (for the unsaturated polyester) and acid-catalysed crosslinking (for the furan resin) to give co-cured composite materials. Although these materials have inferior physical properties, such as low Tg and low storage modulus compared with those of unsaturated polyester and furan resins alone, they show markedly improved flame retardance compared with that of the normally highly flammable unsaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…Char residue at 800 °C was significantly higher for BE‐ESO‐PFA than BE (according to Fisher LSD method). It is related to presence of PFA which has char forming tendency . Derivative weight graph of samples showed higher degradation rate for BE in comparison to BE‐ESO‐PFA that is in good agreement with higher char content of samples.…”
Section: Resultssupporting
confidence: 65%
“…Char residue at 800 °C was significantly higher for BE‐ESO‐PFA than BE (according to Fisher LSD method). It is related to presence of PFA which has char forming tendency . Derivative weight graph of samples showed higher degradation rate for BE in comparison to BE‐ESO‐PFA that is in good agreement with higher char content of samples.…”
Section: Resultssupporting
confidence: 65%
“…In a recently completed project, we demonstrated that UP resins may be made significantly more flame retardant with no detrimental effect to mechanical properties, by blending and co-curing (crosslinking) these with other relatively inexpensive, but more flame retardant, resins such as chemically modified phenolic resins [21][22][23][24][25]. The work described here builds on this experience and extends this technology to the almost equally flammable VE resins, commonly used in marine composites.…”
Section: Introductionmentioning
confidence: 81%
“…These strategies, however, can have deleterious effects on the physical and mechanical properties of the UP and/or can significantly increase material costs. In order to address this problem, we have been investigating a potentially more cost-effective method of flame retarding UPs by co-curing UP with char-forming, and hence more flame-retardant, resins such as phenolic resoles, furan resins and melamine-formaldehyde resins [8][9][10][11][12][13]. Surprisingly, the blending of UP with other resins has hitherto been used mainly to improve surface finish or to decrease mould shrinkage rather than to improve flame retardance [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Our work has demonstrated that whilst flame-retardance may easily be improved by this "blending" approach, it is important that the added resin is co-cured into the matrix if good flame-retardance is to be accompanied by acceptable physical and mechanical properties. Thus furan resins, which do not co-cure with UP, effectively plasticise the UP [12], and simple resoles, which also do not co-cure, lead to phase separated blends displaying two glass-transition temperatures [9]. Of the commercially available resoles so far studied, we have found only allyl-subsituted resoles to be chemically incorporated into the styrene-cured UP matrix (via radical reactions involving the allyl groups) giving homogeneous blends with single glass transition temperatures (T g s), good mechanical properties and acceptable flame retardance [9,10].…”
Section: Introductionmentioning
confidence: 99%